Ethnobotanical study of medicinal plants used in the treatment of neurological disorders in the Western Ghats region of Dakshina Kannada district, Karnataka, India. - A, Yogeesha; G, Krishnakumar (Ethnobotany Research and Applications, 2023)
Background: The incidence of neurological disorders has increased globally over last decade particularly in developing countries. People inhabiting in the remote regions of Dakshina Kannada district are often affected with several kinds of neurological disorders. No specific survey has been carried out for neurological disorders so far, hence the present study was undertaken to document the plants used to treat such disorders. Methods: This study was conducted in Western Ghats region of Dakshina Kannada district, Karnataka, India, during 2018 -2022 to document the ethnomedicinal plants used in the treatment of neurological disorders by the tribal and ethnic groups of this region. This region is considered as a repository of ethnomedicinal wealth for treating various human ailments. Data was collected based on semi-structured questionnaire, interviews and discussions with traditional practitioners. Recorded data were analyzed by conventional methods as well as quantitative ethnobotanical parameters such as Use Value (UV), Relative Frequency of Citation (RFC) and Informants Consensus Factor (ICF). Results: The study provides useful information on 143 plant species belonging to 61 families used to treat neurological disorders such as epilepsy, depression, insomnia, paralysis and psychosis. Among these species, 101 were wild and 42 cultivated. Leaves are widely utilized in the preparation of remedies. The most predominant family was Fabaceae (16 species), and growth form was the trees (56 species). The medicinal plant exhibited highest RFC (0.36) value is Eclipta prostrata. Higher informant consensus factor (ICF) value was reported for psychosis (ICF=0.35) followed by epilepsy (ICF=0.24), insomnia (ICF=0.22), depression (ICF=0.13) and least for paralysis (ICF=0). Conclusion: The medicinal plants were documented with the focus on conserving the ethnic knowledge as documentary evidence for natural herbal product research. This study concluded that medicinal plant species such as Cuminum cyminum, Cynodon dactylon, Rauvolfia serpentina, Vitex negundo and Withania somnifera have been used to treat maximum number of ailments. IUCN status of 143 medicinal plant species showed that, 3 species are in near threatened (NT) category, 5 species vulnerable (VU), 3 species endangered (EN), 48 are in least concern (LC) category, 2 species are in data deficient (DD) category and the status is not evaluated (NE) for 82 species. Keywords: Folk medicine, Western Ghats, Neurological disorders, Tribal communities, Conservation status